Mind-Sets of Worried Citizens and the ‘Real-World Experiment’ of Covid-19: A Mind Genomics Cartography - Moskowitz, Howard; Prendi, Voltiza; Gere, Attila; Harizi , Ariola; Papajorgji , Petraq (Edelweiss Applied Science and Technology, 2020)
Two groups of 51 US respondents each evaluated combinations of statements about the problems and solutions that a country might face. The two studies were run a year apart, May 2019 (before the Covid-19 pandemic) and May 2020 (at the then current height of the pandemic). The problems and solutions were combined by experimental design, creating a unique set of 24 vignettes for each respondent. The responses to the vignettes (negative versus positive outcome, based on the vignette) were deconstructed to the contribution of each of the 16 elements (four problems, 12 solutions). Three mind-sets emerged, based on clustering the pattern of responses to the 16 elements from each of the 100 respondents: MS1–Startups, students; MS2–Change and Investment; MS3–Family social. Each mind-set shows a specific pattern of responses to problems, solutions, and the effect of Covid-19. The granularity afforded by Mind Genomics allows the researcher a new and profoundly deeper understanding of the mind of the citizen, opening a new area of psychological science. The three mind-sets distribute similarly through the population, requiring short intervention, the Personal Viewpoint Identifier, a set of six questions, the pattern of response to which assigns a new person to one of the three mind-sets.